Anti‐inflammatory properties of conditioned medium from human Wharton’s jelly mesenchymal stem cells - Azis, Rizal; Widowati, Wahyu; Gunanegara, Rimonta Febby; Kusuma, Hanna Sari Widya; Triharsiwi, Dwi Nur; Hadiprasetyo, Dhanar Septyawan; Gondokesumo, Marisca Evalina; Mars, Nicholas (Universitas Gadjah Mada, 2025)
Acute respiratory distress syndrome (ARDS) is a critical respiratory dysfunction triggered by intense in‐ flammation, microvascular damage, and increased epithelial and pulmonary vascular permeability. Human Wharton’s jelly mesenchymal stem cells (hWJMSCs) possess regenerative and anti‐inflammatory activities through the cytokines, chemokines, and growth factor secretion. The development of anti‐inflammatory agents derived from hWJMSCs has become one of the therapeutic solutions. Instead of direct cell use of hWJMSCs, their conditioned medium (CM) provides a cell‐free approach that delivers bioactive factors while minimizing the risks associated with stem cell transplantation. This study aims to measure the levels of vascular endothelial growth factor‐α (VEGF‐α), epidermal growth factor‐β (EGF‐β), interleukin‐10 (IL‐10), and hepatocyte growth factor (HGF) in CM‐hWJMSCs under non‐starvation and starvation conditions (24, 48 and 72 hours) using ELISA. The anti‐inflammatory potential of these factors was then analyzed through molecular docking with pro‐inflammatory cytokines. VEGF‐α, EGF‐β, IL‐10 and HGF levels were measured across all conditions. VEGF‐α ranged from 2590.37 to 3613.92 ng/mg protein; EGF‐β 347.01–504.43 ng/mg; IL‐10 302.59–729.28 pg/mg; and HGF 1747.20–2903.52 ng/mg. The molecular docking revealed strong binding between VEGF‐α, EGF‐β, IL‐10 and HGF with pro‐inflammatory cytokines, namely IL‐1β, IL‐6 and TNF‐α. VEGF‐α had the strongest bond with TNF‐α (–1162.3 kJ/mol), while EGF‐β formed the most hydrophobic and hydrogen interactions. The findings suggest that CM‐hWJMSCs, enriched with anti‐inflammatory and regenerative cytokines, may serve as a promising candidate for modulating the inflammatory pathways involved in ARDS pathogenesis. Longer starvation increased the secretion of VEGF‐α, EGF‐β, IL‐10 and HGF. These factors are known to promote angiogenesis, regulate immune responses, and protect against epithelial injury, thereby supporting the anti‐inflammatory and regenerative potential of hWJMSCs‐CM for ARDS therapy.